2017
DOI: 10.1002/chem.201704584
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Syndiospecific (Co)Polymerization of Fluorostyrene with High Monomer Conversion

Abstract: Fluoromonomers are difficult to polymerize through a coordination mechanism owing to the strong chelation between fluorine and catalysts and the electron-deficient double-bond. We report herein the unprecedented polymerization of para-fluorostyrene (pFS) with excellent activity (1.12×10 g mol h ), distinguished syndioselectivity (rrrr >99 %) and high conversion (98.4 %) using rare-earth-metal catalysts bearing a pyridyl methylene fluorenyl ligand. DFT calculations reveal polar fluorine loses overwhelming coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…First, the copolymerization of p-fluorostyrene ( pFS) and butadiene (BD) in toluene at room temperature was investigated by using the catalytic systems of 1/[Ph 3 C][B(C 6 F 5 ) 4 ]/[Al i Bu], which are highly active towards the homopolymerization of pFS and the copolymerization with styrene and ethylene, respectively. 25,26 The polymerization catalyzed by 1a (Flu cent -Sc-N (96.26°)) occurred fast but gave a copolymer insoluble in many solvents even under a high temperature of 160°C. We proposed that cross-linking took place, since the scandium active species is Lewis acidic and can initiate polymerization of the dangling CvC bonds of the 1,2-regulated PBD segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the copolymerization of p-fluorostyrene ( pFS) and butadiene (BD) in toluene at room temperature was investigated by using the catalytic systems of 1/[Ph 3 C][B(C 6 F 5 ) 4 ]/[Al i Bu], which are highly active towards the homopolymerization of pFS and the copolymerization with styrene and ethylene, respectively. 25,26 The polymerization catalyzed by 1a (Flu cent -Sc-N (96.26°)) occurred fast but gave a copolymer insoluble in many solvents even under a high temperature of 160°C. We proposed that cross-linking took place, since the scandium active species is Lewis acidic and can initiate polymerization of the dangling CvC bonds of the 1,2-regulated PBD segments.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] We reported for the first time the coordination homo-and copolymerizations of polar styrene monomers including methoxystyrene (MOSt) and halogen substituted styrenes with the use of side-armed half-sandwich rare-earth metal complexes, with styrene exhibiting high activity and stereoselectivity. [23][24][25] Thereafter copolymers composed of polar styrenes/ethylene and anisylpropylenes/ethylene were obtained. [26][27][28] With respect to polar dienes, copolymerization of 2-(2-methylidenebut-3-enyl)furan (MBEF) with isoprene without a masking reagent was achieved by using the bis ( phosphino)carbazolideyttrium precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, extensive studies have been devoted to develop efficient “single‐site” catalytic systems for stereospecific polymerization of styrene and its derivatives, and various homogeneous metallocene, half‐metallocene, and non‐metallocene group 3 and 4 metal‐based catalysts have been invented . In the meantime, syndiotactic polystyrene derivatives bearing polar groups such as halogen, alkoxyl, aminoalkyl, and methylthio etc., that provide polymers with improved surface properties, adhesive properties, affinity for dyes, and compatibility with other polar polymers, have been successfully prepared …”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found that rare‐earth metal catalysts supported by pyridyl methyl fluorenyl ligand demonstrated their superiority on selective and controlled coordination polymerization of styrene derivatives bearing various electron‐donating/withdrawing substituents . With the help of these powerful constrained geometry configuration (CGC) catalysts, we successfully synthesized a series of high syndiotactic polystyrene derivatives such as poly(methoxystyrene), poly(4‐Methylthiostyrene), poly(4‐fluorostyrene) etc . In this contribution, we report that coordination polymerizations of 1VN, 2VN, and MVN were carried out by using the half‐sandwich scandium precursor 1 and the CGC rare‐earth metal precursors 2a ‐ 2c ( Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, rare‐earth metal based catalytic systems have been reported to be extraordinary tolerance toward polar groups, which exhibit high activity and excellent stereo‐selectivity for homo‐ and copolymerizations of polar styrenes. [ 17,18,27–34 ] We report herein the coordination polymerization of BN2VN using a series of half‐sandwich or constrained‐geometry‐configuration (CGC)‐type scandium catalysts ( Figure ) with high activity and distinguished syndioselectivity to give high molecular weight products, which can be transferred to highly syndiotactic poly(vinyl alcohol). The influences of steric hindrance of ligands and polymerization conditions on the catalyst performances as well as structures of the resultant products are investigated.…”
Section: Figurementioning
confidence: 99%